The 2019 people's verdict in Goa: lessons for the BJP - Shrinagare, Alaknanda (Social Science in Perspective)
While the BJP swept many states of India. It is a mixed result for BJP in Goa. Goa retained its old equation with South goa seat won by the BJP and North Goa by the congress. The BJP could not repeat its 2014 victory in Goa. The slide of BJP in 2019 Lok Sabha election can by attributed to the death of Manohar Parrikar, internal conflicts among the coalition partners of BJP and the unfulfilled promises of the BJP made in the past. - Reproduced